Forecast combination based on multiple encompassing tests in a macroeconomic DSGE system - Mauro Costantini; Ulrich Gunter; Robert M. Kunst (Institute for Advanced Studies (IHS), 2010)
We use data generated by a macroeconomic DSGE model to study the relative benefits of forecast combinations based on forecast-encompassing tests relative to simple uniformly weighted forecast averages across rival models. Assumed rival models are four linear autoregressive specifications, one of them a more sophisticated factor-augmented vector autoregression (FAVAR). The forecaster is assumed not to know the true data-generating DSGE model. The results critically depend on the prediction horizon. While one-step prediction hardly supports test-based combinations, the test-based procedure attains a clear lead at prediction horizons greater than two.
Keywords: C15; C32; C53; 330; combining forecasts; encompassing tests; model selection; time series; DSGE model; Prognoseverfahren; Statistischer Test; Modellierung; Zeitreihenanalyse; Dynamisches Gleichgewicht; Theorie